The stench of knowledge: The Vilain dreamer in Les Serées by Guillaume Bouchet - Kenny, N (Taylor and Francis, 2017)
Guillaume Bouchet wrote 36 conversations which he presents as taking place in Poitou at convivial evening gatherings (or ‘Serées’). Each conversation has a theme. That of the sixteenth Serée (first published in 1597) is dreams. The debate is triggered as usual by an incident that has just occurred within the fictional frame: the host refused to invite someone that evening who had turned up earlier in the day and tried to cadge an invitation by claiming to have dreamed that the host was roasting a pig (as indeed he was). The debate proceeds smoothly, but after several pages it is rudely interrupted by a wisecracker, described as ‘vilain’. He is intent on telling everyone about a recent dream in which he soiled himself. This disgusts the listeners and disrupts the erudite exchange of learned commonplaces about dreams. Unusually for an event within the fictional frame of one Serée, it also occasions the theme of the next one, which begins with the assembled guests refusing to sit nearer the joker in case he still smells. Bouchet uses this vilain figure to foster the distinctively unsettling but constructive epistemology of the Serées, and to represent knowing as inseparable from having a body, from having faculties that straddle body and mind, and from being a social animal.